Does the initial GCS of patients with brain arteriovenous malformations impact their postoperative functional outcomes? A single-center study experience and literature review - Alireza Tabibkhooei; Mansour Parvaresh; Mehdi Haghshenas; Mohammad Yavari; Kimia Didehvar; Parisa Javadnia (Egyptian Journal of Neurosurgery, 2025)
Abstract Aim Brain arteriovenous malformations (AVMs) represent a complex vascular anomaly that carries a significant risk of complications. The Spetzler–Martin (SM) grading system and its supplementary variant (supp-SM) have been developed to estimate surgical risk; however, there remains a lack of consensus regarding grading systems that can accurately predict patient outcomes. Method This study evaluated a cohort of 26 patients with brain AVM who underwent surgical resection at a single institution over seven years. The primary clinical and imaging characteristics of the patients were assessed. Utilizing Python for data analysis, this study aimed to identify correlations among the SM and supp-SM grading, Glasgow Coma Scale (GCS) scores, postoperative Karnofsky Performance Scale (KPS), duration of intensive care unit admission, and intraoperative blood loss. In addition, we did a literature review on AVM surgical outcomes. Results Incorporating GCS into the supp-SM grading framework significantly enhanced the predictive ability regarding intraoperative blood loss and KPS at discharge compared to using the SM or supp-SM grading in isolation. Conclusion The combination of supp-SM grading and GCS is a more reliable indicator of postoperative outcomes for patients with brain AVMs. Nevertheless, additional longitudinal studies are required to substantiate this conclusion further.